MULTIPROFESSIONAL CARE IN CHILDCARE CONSULTATIONS - Silvestre Pereira, Andressa Marcelly (Cadernos ESP, 2023)
To report, from the perspective of the Resident Nurse, the experience in childcare services shared with a multidisciplinary team in a municipality in Rio Grande do Norte. Study of the experience report type on multidisciplinary care provided during childcare consultations, between November 2021 and May 2022, in a health unit in the city of Mossoró. Within the Family Health Strategy (ESF), the care provided by the multidisciplinary team can optimize the consultation, discussing essential points, based on the specific needs of children. In order to provide a more complete service, shared consultations were carried out with the presence of a maximum of 3 professionals from different categories. In the period in question, a total of 138 consultations were carried out, of which 48 were in the shared modality. This consultation mode provided a more dynamic and equitable service, with a better clinical evaluation of the child, streamlining the service, identifying specific needs and providing the correction of conducts in a timely manner, ensuring follow-up at the UBS level, contributing to reduce the RAS burden.
Keywords: Family Health Strategy; Childcare; Multiprofessional team